ISO 9001 quality management systems - Natarajan, Dhanasekharan (Springer, 2017)
This book explains the requirements of ISO 9001 for establishing quality management system (QMS) for an organization. The requirements are illustrated with examples from industries for understanding the requirements and preparing the documents of QMS with high clarity. Methods of integrating ISO 9001 requirements with enterprise resource planning (ERP) software are presented. The software integrated approach enables process owners to focus on their core tasks of achieving the planned outputs of processes and the software generates quality records automatically.
Keywords: ISO 9001 Standard.; Quality assurance -- Management.; elektronické knihy; electronic books